Ischemia/reperfusion-activated ferroptosis in the early stage triggers excessive inflammation to aggregate lung injury in rats - Liu, Xiujie; Pan, Binhui; Wang, Xiaoting; Xu, Junpeng; Wang, Xinyu; Song, Zhengyang; Zhang, Eryao; Wang, Fangyan; Wang, Wantie (Frontiers in Medicine, 2023)
Objective Lung ischemia/reperfusion injury (LIRI) is a clinical syndrome of acute lung injury that occurs after lung transplantation or remote organ ischemia. Ferroptosis and inflammation are involved in the pathogenesis of LIRI according to the results of several studies on animal models. However, the interactive mechanisms between ferroptosis and inflammation contributing to LIRI remain unclear. Methods HE staining and indicators of oxidative stress were used to evaluated the lung injury. The reactive oxygen species (ROS) level was examined by DHE staining. The quantitative Real-time PCR (qRT-PCR) and western blot analysis were employed to detect the level of inflammation and ferroptosis, and deferoxamine (DFO) was used to assess the importance of ferroptosis in LIRI and its effect on inflammation. Results In the present study, the link of ferroptosis with inflammation was evaluated at reperfusion 30-, 60- and 180-minute time points, respectively. As the results at reperfusion 30-minute point shown, the pro-ferroptotic indicators, especially cyclooxygenase (COX)-2 and acyl-CoA synthetase long-chain family member 4 (ACSL4), were upregulated while the anti-ferroptotic factors glutathione peroxidase 4 (GPX4), cystine-glumate antiporter (XCT) and ferritin heavy chain (FTH1) were downregulated. Meanwhile, the increased level of interleukin (IL)-6, tumor necrosis factor alpha (TNF-α) and IL-1β were observed beginning at reperfusion 60-minute point but mostly activated at reperfusion 180-minute point. Furthermore, deferoxamine (DFO) was employed to block ferroptosis, which can alleviate lung injury. Expectedly, the survival rate of rats was increased and the lung injury was mitigated containing the improvement of type II alveolar cells ultrastructure and ROS production. In addition, at the reperfusion 180-minute point, the inflammation was observed to be dramatically inhibited after DFO administration as verified by IL-6, TNF-α and IL-1β detection. Conclusion These findings suggest that ischemia/reperfusion-activated ferroptosis plays an important role as the trigger for inflammation to further deteriorate lung damages. Inhibiting ferroptosis may have therapeutic potential for LIRI in clinical practice.